Stability of ferroic phases in the highly piezoelectric Pb(ZrxTi1 x)O3 ceramics - Dhananjai Pandey; Akhilesh Kumar Singh; Sunggi Baik (International Union of Crystallography, 2007)
The morphotropic phase boundary in the phase diagram of the technologically important Pb(ZrxTi1-x)O3 (PZT) ceramics has been traditionally believed to separate ferroelectric tetragonal and rhombohedral phase regions. This old picture has come under close scrutiny during the last eight years following the discovery of new monoclinic phases in the Cm and Cc space groups. This article presents a brief overview of these discoveries in which the use of multiple diffraction probes (X-ray, electron, neutron diffraction) in conjunction with physical property measurements has played a crucial role. A new phase diagram of PZT showing the stability fields of these structures below room temperature is also presented. © International Union of Crystallography 2008.